Loss of function mutations in RPL27 and RPS27 identified by whole‐exome sequencing in Diamond‐Blackfan anaemia. (25th November 2014) - Wang, RuNan; Yoshida, Kenichi; Toki, Tsutomu; Sawada, Takafumi; Uechi, Tamayo; Okuno, Yusuke; Sato‐Otsubo, Aiko; Kudo, Kazuko; Kamimaki, Isamu; Kanezaki, Rika; Shiraishi, Yuichi; Chiba, Kenichi; et al.
Summary Diamond‐Blackfan anaemia is a congenital bone marrow failure syndrome that is characterized by red blood cell aplasia. The disease has been associated with mutations or large deletions in 11 ribosomal protein genes including RPS7, RPS10, RPS17, RPS19, RPS24, RPS26, RPS29, RPL5, RPL11, RPL26 and RPL35A as well as GATA1 in more than 50% of patients. However, the molecular aetiology of many Diamond‐Blackfan anaemia cases remains to be uncovered. To identify new mutations responsible for Diamond‐Blackfan anaemia, we performed whole‐exome sequencing analysis of 48 patients with no documented mutations/deletions involving known Diamond‐Blackfan anaemia genes except for RPS7, RPL26, RPS29 and GATA1. Here, we identified a de novo splicing error mutation in RPL27 and frameshift deletion in RPS27 in sporadic patients with Diamond‐Blackfan anaemia. In vitro knockdown of gene expression disturbed pre‐ribosomal RNA processing. Zebrafish models of rpl27 and rps27 mutations showed impairments of erythrocyte production and tail and/or brain development. Additional novel mutations were found in eight patients, including RPL3L, RPL6, RPL7L1T, RPL8, RPL13, RPL14, RPL18A and RPL31. In conclusion, we identified novel germline mutations of two ribosomal protein genes responsible for Diamond‐Blackfan anaemia, further confirming the concept that mutations in ribosomal protein genes lead to Diamond‐Blackfan anaemia.